The future of motherhood in western societies late fertility and its consequences - Beets, Gijs; Schippers, Johannes Jan; Velde, Egbert R. te (Springer Netherlands, 2011)
This book offers a holistic overview of the process of postponement and its background in modern Western societies both at the personal and societal levels. It includes contributions from reproductive, evolutionary biological and neurological sciences as well as from the fields of demography, economics, sociology and psychology. It argues that governments could support couples by a cafeteria-like set of arrangements from which one can compose a package according to personal preferences that can facilitate to a break in the rising age of first motherhood.